"I have a name, I am not mop trolley"; The working relationships in the operating theatre at a selected academic hospital. (2020) - Aphane, M.S.; Khumisi, E.T.; Mogale, R.S.
Abstract: In healthcare settings, working relationships are linked to continuity of care and patient safety especially in specialized units such as operating theatres. Purpose of the research: This study explores and describes working relationships between nurses and general assistants in the operating theatre. Methods and procedures: This qualitative study used a case study design comprised of four focus group discussions to collect data. Data were analysed using the ten steps of content analysis. Results: Three main themes emerged from the focus group discussions: disrespect and mistrust as the core of working relationships between nurses and general assistants, poor communication in healthcare teams and generic versus specialised roles. Conclusions: Following identification of challenges, participants indicated that healthy working relationships should be cultivated by treating contemporaries with respect, using open communication and clear division of labour. Participants recommended using innovative communication strategies to optimize working relationships in this digital age especially in specialized areas such as operating theatre where patient continuity and safety are essential.